N028 Audit of compliance with intravenous (IV) iron dosing and evaluation of the IV service in patients with inflammatory bowel diseases (IBD) at Antrim Area Hospital, UK. (16th January 2018) - Kearns, J; Jacob, G
Abstract: Background: The local guidelines on the management of iron deficiency anaemia at Antrim Area Hospital, UK, have adopted the recommendation of the relevant 2015 ECCO Guidelines for a simplified approach to estimate iron need. Based on haemoglobin (Hb) and weight, patients receive 1000, 1500, or 2000 mg of iron. Iron isomaltoside is an intravenous (IV) iron introduced to our hospital in October 2016, and allows delivery of high doses of up to 20 mg of iron per kg of body weight in a single administration. The purpose of this audit was to examine compliance against the guideline recommendation on dosing and to evaluate our IV iron service Methods: The medical records of patients who received iron isomaltoside between October 16 and October 17 were retrospectively examined, and data on demographics, IV iron dose, Hb/iron parameters and adverse drug reactions was collected. An initial audit took place between October 2016 and April 2017, amendments were made based on observations, and an additional audit was conducted for the period May 2017 to October 2017. Results: Sixty-three patients received iron isomaltoside in the total audit period; 49/63 (78%) were females. Mean weight was 70 kg, baseline Hb 98 g/l (range 73–135), ferritin 28 µg/l (2–160), and 8% of patients had a Hb of ≥ 120 g/l. Compliance with guideline dosing recommendations was achieved in 82% of cases in the first audit, while 18% of patients were underdosed. Compliance increased to 100% in the second audit. Mean IV iron dose was 1278 mg; with 49% of patients receiving > 1000 mg, and 65% treated in one appointment. A total of 85 administrations took place; 14 fewer compared with the administrations that would have been needed with our previous IV iron. Mean post-infusion Hb and ferritin were 119 g/l and 198 µg/l, respectively. Hb rose from 99 to 123 g/l in patients that received their dose as per protocol, while a smaller increase from 95 to 110 g/l was observed in patients who were underdosed. The proportion of patients achieving a Hb of ≥ 120 g/l post IV iron was 64% and 36% in patients receiving the recommended vs. a lower iron dose, respectively. Two adverse drug reactions (nausea and blisters) took place in 85 administrations (2.3%). Both reactions were mild and patients were able to receive their total dose after re-starting the infusion. Conclusions: 100% of compliance with the recommended dosing regimen was achieved after the initial audit. Patients who were dosed appropriately achieved higher Hb increases indicating that patients with IBD have high iron needs and highlighting the importance of complying with the ECCO guideline recommendations on dosing. Iron isomaltoside was efficacious, convenient, and well tolerated.